Image Guided Core Needle Biopsy (CNB) in Malignancy of The Breast—Part 2: Breast Ductal Malignancies other than Ductal Carcinoma In Situ (DCIS) and Invasive Ductal Carcinoma (IDC) - Bhothisuwan, MD, Wilaiporn; Pantawanant, MD, Niramon; Marukatat, MD, Naruporn; Kimhamanon, RT, Pramaporn (The Bangkok Medical Journal, 2021)
Breast lesions, both palpable and non-palpable may represent tumours, which can be benign, malignant, or a specific high risk lesion. Breast imaging is advised in order to detect and define lesions and its extension. It is compulsory to have pathological tissue diagnosis prior to surgical management. Breast ultrasound is our routine study in conjunction with mammography. The most common ultrasound (US) appearances of malignant breast mass are heterogeneous hypoechoic mass with angular or ill-defined margins and changes of posterior acoustic shadowing. This paper shows core needle biopsy (CNB) results of lobular carcinoma (LC) and ductal carcinoma with satellitosis, bilateral guided CNB, with nodal metastasis, mucinous carcinoma (MC) with diffuse intraductal papillomatosis, contralateral metastasis from MC and MC with contralateral IDC. The cases showed different clinical presentations and interesting examples of manifestation.